Mathematical Software : Proceedings of the First International Congress of Mathematical Software, Beijing, China 17-19 August 2002. - Cohen, Arjeh M. (World Scientific Publishing Company, 2002)
The advent of mathematical software has been one of the most important events in mathematics. Mathematical software systems are used to construct examples, to prove theorems, and to find new mathematical phenomena. On the other hand, mathematical research often motivates developments of new algorithms and new systems. This volume contains the papers presented at the First International Congress of Mathematical Software, which aimed at a coherent study of mathematical software systems from a wide variety of branches of mathematics. The book discusses more than one hundred mathematical software.